Nitrogen Source Matters: High NH4/NO3 Ratio Reduces Cannabinoids, Terpenoids, and Yield in Medical Cannabis - Saloner, Avia; Bernstein, Nirit (Frontiers in Plant Science, 2022)
The N form supplied to the plant, ammonium (NH4+) or nitrate (NO3–), is a major factor determining the impact of N nutrition on plant function and metabolic responses. We have hypothesized that the ratio of NH4/NO3 supplied to cannabis plants affects the physiological function and the biosynthesis of cannabinoids and terpenoids, which are major factors in the cannabis industry. To evaluate the hypothesis we examined the impact of five supply ratios of NH4/NO3 (0, 10, 30, 50, and 100% N-NH4+, under a uniform level of 200 mg L–1 N) on plant response. The plants were grown in pots, under controlled environment conditions. The results revealed high sensitivity of cannabinoid and terpenoid concentrations and plant function to NH4/NO3 ratio, thus supporting the hypothesis. The increase in NH4 supply generally caused an adverse response: Secondary metabolite production, inflorescence yield, plant height, inflorescence length, transpiration and photosynthesis rates, stomatal conductance, and chlorophyll content, were highest under NO3 nutrition when no NH4 was supplied. Ratios of 10–30% NH4 did not substantially impair secondary metabolism and plant function, but produced smaller inflorescences and lower inflorescence yield compared with only NO3 nutrition. Under a level of 50% NH4, the plants demonstrated toxicity symptoms, which appeared only at late stages of plant maturation, and 100% NH4 induced substantial plant damage, resulting in plant death. This study demonstrates a dramatic impact of N form on cannabis plant function and production, with a 46% decrease in inflorescence yield with the increase in NH4 supply from 0 to 50%. Yet, moderate levels of 10–30% NH4 are suitable for medical cannabis cultivation, as they do not damage plant function and show only little adverse influence on yield and cannabinoid production. Higher NH4/NO3 ratios, containing above 30% NH4, are not recommended since they increase the potential for a severe and fatal NH4 toxicity damage.